2014
DOI: 10.1215/00127094-2649534
|View full text |Cite
|
Sign up to set email alerts
|

Inverse problem for the Riemannian wave equation with Dirichlet data and Neumann data on disjoint sets

Abstract: We consider the inverse problem to determine a smooth compact Riemannian manifold with boundary (M, g) from a restriction Λ S,R of the Dirichlet-to-Neumann operator for the wave equation on the manifold. Here S and R are open sets in ∂M and the restriction Λ S,R corresponds to the case where the Dirichlet data is supported on R + × S and the Neumann data is measured on R + × R. In the novel case where S ∩ R = ∅, we show that Λ S,R determines the manifold (M, g) uniquely, assuming that the wave equation is exac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 42 publications
(74 reference statements)
2
84
0
Order By: Relevance
“…For the convenience of the reader, we give a proof of the following lemma. An analogous lemma is stated in [28] without a proof.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For the convenience of the reader, we give a proof of the following lemma. An analogous lemma is stated in [28] without a proof.…”
Section: Introductionmentioning
confidence: 98%
“…As described in the scalar valued case in Section 4.4 of [28], in order to determine the cut distance σ Γ from the restricted Dirichlet-to-Neumann map, we need to use a perturbation argument that is based on a refined version of approximate controllability and modified domains of influence. Let Γ ⊂ ∂M and h : Γ → R, and define…”
Section: Introductionmentioning
confidence: 99%
“…Following [39] we assume that µ k = 1 and q k = 0 identically, and that both (M k , g k ), k = 1, 2, satisfy the spectral inequality λ k,n ≤ C ψ k,n,p 2 L 2 (S in ) , (5.5) where the constant C > 0 is independent of n and p. Hassell and Tao [27] showed that all non-trapping Riemannian manifolds (M k , g k ) satisfy (5.5) when S in is replaced by ∂M k . Moreover, (5.5) follows from (and is strictly weaker than) the geometric control condition by Bardos, Lebeau and Rauch [2], see [39]. We will now give a reduction to the result in [39].…”
mentioning
confidence: 99%
“…Below C > 0 denotes a constant that may grow between inequalities, and that depends only on m, C 0 , C 1 , L. Lemma 1 gives us f δ for which u f δ (x, T ) = w δ (x). Thus (38) implies…”
Section: Let Us Definementioning
confidence: 98%